Handgrip weakness and overall life satisfaction decline: derivation of cutoff values and analysis of sex differences in older Chinese adults - Yin, Liangyu; Zhong, Lan (Frontiers in Nutrition, 2025)
Background and aimsHandgrip strength (HGS) is a cost-effective indicator of skeletal muscle function. However, the sex-specific association between HGS and life satisfaction decline among older Chinese adults remains largely unknown.MethodsThis observational, cross-sectional multicenter study included 3,649 older adults (age range: 60–101 years) from a nationally representative survey in China. Overall life satisfaction was determined using a life satisfaction score (LSS). Correlations between variables were examined using a Spearman’s correlation analysis. Receiver operating characteristic (ROC) curves were utilized to determine the HGS cutoffs for predicting a decline in LSS. Restricted cubic spline (RCS) analysis and multivariate logistic regression were employed to investigate the associations between low HGS and LSS.ResultsThis study included 1,762 women and 1,887 men (median age = 68.3 years). LSS decline was observed in 485 (13.3%) participants. HGS was positively correlated with LSS in both men and women (both P < 0.05). Individuals with low HGS were associated with a higher rate of LSS decline (16.2% vs. 10.8%, P < 0.001). RCS analysis demonstrated a linear-like association between HGS and life satisfaction in men (P < 0.001, P nonlinear = 0.099), but not in women (P = 0.110, P nonlinear = 0.329). ROC analysis revealed that the optimal HGS cutoff for indicating the presence of LSS was 27.5 kg for men and 22.3 kg for women. Multivariable analysis showed that participants with low HGS had higher odds of experiencing a decline in LSS [odds ratios (OR) = 1.509, 95% confidence interval (CI) = 1.218–1.867]. This association was observed only in men (OR = 1.871, 95% CI = 1.358–2.562, P < 0.001), while it was attenuated in women (OR = 1.281, 95% CI = 0.964–1.701, P = 0.087).ConclusionThis study establishes sex-specific cutoffs of HGS for identifying a decline in LSS among older Chinese adults. Low HGS is positively associated with LSS decline among men in a linear-like manner, but not among women. These findings might facilitate the development of strategies to promote healthy aging.